2022
DOI: 10.1002/qre.3087
|View full text |Cite
|
Sign up to set email alerts
|

A novel CRITIC‐TOPSIS approach for optimal selection of software reliability growth model (SRGM)

Abstract: Various Software Reliability Growth Models (SRGMs) have been developed over last five decades to estimate the failure rate, software reliability and remaining number of faults in the software during testing phase of software development life cycle. There are numerous SRGMs available in the research literature and in the presence of numerous SRGM, appropriate selection is a staggering task for the software testing professionals. In the software reliability area, researchers have always been interested to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In MCDM, the most important issue is determining weights based on these criteria. Singh [27] recommended an approach using Monte Carlo simulation, and Saxena et al [28], Kumar et al [29], and Grag et al [30] used the entropy method to determine the criteria weights, and a technique for order preference by similarity to an ideal solution (TOPSIS) method was used to rank the criteria of SRMs. Our proposed integrated MCDMR reflects the ranking of each suitability among the methods to determine the weights.…”
Section: Multi-criteria Decision Methods Using Rankingmentioning
confidence: 99%
“…In MCDM, the most important issue is determining weights based on these criteria. Singh [27] recommended an approach using Monte Carlo simulation, and Saxena et al [28], Kumar et al [29], and Grag et al [30] used the entropy method to determine the criteria weights, and a technique for order preference by similarity to an ideal solution (TOPSIS) method was used to rank the criteria of SRMs. Our proposed integrated MCDMR reflects the ranking of each suitability among the methods to determine the weights.…”
Section: Multi-criteria Decision Methods Using Rankingmentioning
confidence: 99%
“…CRITIC's integration with the grey relational analysis for investment portfolio selection [43] and its implementation in the virtual reality metaverse for customer requirements ranking [44] demonstrated CRITIC's adaptability to different decision-making contexts. Saxena et al [45] demonstrated the importance of CRITIC in software engineering, particularly in the best selection of reliability growth models. Vadivel et al [46] emphasized the importance of CRITIC in sustainable supply chain management; i.e.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Lee, Chang, and Pham (2020) presented a new SRGM including software failures that are interdependent. Few researchers have also used Multi-criteria decision making (MCDM) in SRGMs for the ranking of models (Bibyan and Anand 2022; Kumar, Saxena and Garg 2021;Saxena, Kumar and Ram 2022;Saxena, Kumar and Ram 2021).…”
Section: Introductionmentioning
confidence: 99%